2021
DOI: 10.2217/fvl-2021-0090
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Blood Groups and COVID-19 Outcome in Iranian Patients

Abstract: Aim: Many factors have been speculated to explain the COVID-19 complex clinical phenotype. Due to the inconsistent data published on blood groups and COVID-19, we conducted a study on Iranian patients to further assess this association. Materials & methods: This retrospective study was conducted on data collected from confirmed COVID-19 hospitalized patients during March and December 2020 in a referral hospital for COVID-19, 5 Azar Hospital, Gorgan, north of Iran. A total of 1554 confirmed COVID-19 cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…In accordance with our data, investigations from Iran, Iraq, Turkey, Denmark, and Lebanon indicated that blood group A had the largest proportion of COVID-19-positive cases and mortality than the other blood groups, and that the O blood group had the lowest number of infected individuals [13][14][15][16][17]. In contrast, a number of studies carried out in a variety of nations found no connection between the ABO blood groups and the severity of COVID-19 or the mortality rate [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with our data, investigations from Iran, Iraq, Turkey, Denmark, and Lebanon indicated that blood group A had the largest proportion of COVID-19-positive cases and mortality than the other blood groups, and that the O blood group had the lowest number of infected individuals [13][14][15][16][17]. In contrast, a number of studies carried out in a variety of nations found no connection between the ABO blood groups and the severity of COVID-19 or the mortality rate [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Higher mRNA and protein levels of ACE2 are observed in individuals with fundamental heart failure, suggesting an increased likelihood of severe COVID-19 in patients with primary cardiovascular disease [ 148 ]. Diabetic patients, due to the involvement of the PPAR signaling pathway in SARS-CoV-2 intrusion through the ACE2 receptor, exhibit greater vulnerability to COVID-19 infection [ 16 , 149 ]. Moreover, pancreatic islets of type 2 diabetes mellitus patients show significantly elevated ACE2 expression compared to healthy subjects [ 150 ].…”
Section: Pathogenesis Of Sars-cov-2 In Individuals With Pre-existing ...mentioning
confidence: 99%
“…Polymorphisms in various receptors and co-receptors of SARS-CoV-2, influencing the virus's entry into diverse tissues among different individuals, may contribute to the observed clinical variability in the disease across subjects [ 15 ]. Unfortunately, the restricted understanding of the human molecular targets of SARS-CoV-2 hinders the development of host-dependent personalized therapies [ 16 ]. In this study, our objective is to bridge this knowledge gap by examining recent findings related to a crucial stage in viral infection, specifically the entry mechanisms of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…However, others have estimated a higher SARS-CoV-2 risk in subjects with B or AB groups [ 12 ]. On the other hand, no associations were described among hospitalizations, severity, and death of COVID-19 cases and ABO [ 13 , 14 , 15 , 16 , 17 , 18 ], but some exceptions have been reported [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%